Acute unintentional mercuric compound self-poisoning - case report - Ristić, Snežana; Paripović, Aleksandra; Sarajlija, Adrijan; Kovačević, Branko; Sudji, Jan (Archives of Pharmacy, 2022)
Acute poisoning of children, especially under the age of 6, is a global health problem. Among the most common poisoning causes in children are medicines, cosmetic products, household hygiene products, and numerous other chemicals. This paper aimed to present a case of acute poisoning of a 19-month-old child who unintentionally ingested an unknown amount of mercuric compound and soon showed hematemesis, melena and acute renal failure. Since admission, it has been treated with continuous hemodiafiltration in combination with chelation therapy. Anuria persisted for 7 days, and complete recovery of renal function (estimated based on serum urea and creatinine concentration) occurred after 10 days of admission. Continuous hemodiafiltration was performed for 13 days in order to more efficiently eliminate mercury and the chelating agent complex. The applied treatment reduced the concentration of mercury in the blood from 4500 μg/L on admission, to 63,6 μg/L after three weeks of treatment. One month after ingestion, she showed a toxic reaction to chelating agent in the form of diffuse erythema and elevated serum transaminases. It was treated with immunoglobulins, with regression of skin changes and normalization of transaminases after 5 days. During the two-year follow-up it was healthy and with normal development, with no signs of lasting consequences due to acute mercury poisoning. The presented case of self-poisoning is also the first ever known case of mercury poisoning in Serbia. This indicates the necessity of constant supervision by parents or guardians, as well as adequate storage and disposal of toxic substances in the household.